PENDIDIKAN DAN BIMBINGAN KECAKAPAN HIDUP (LIFE SKILL) PESERTA DIDIK - Mislaini, Mislaini (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
Education must reflect the values ​​of everyday life, both preservative and progressive. So that educational institutions should merge with real-life values ​​that exist in the environment. For this reason life skill education (life skill) undoubtedly to be applied and applied for students in any educational institutions tingakat. The development of life skills values ​​in various activities in educational institutions both in classroom learning, as well as in extracurricular activities, and in religious activities is expected to foster unyielding spirit with high work ethic, creative independence, innovative in creating works in all Field, so that in the end able to create human resources that qualified for the surrounding community.